Puzzling Techniques: A Way Forward for Mastering the Islamic Finance / Shahsuzan Zakaria...[et al.] - Zakaria, Shahsuzan; Marzuki, Marziana Madah; Mohd Zawawi, Mohd Zafian Mohd Zawawi; Zakaria, Razimi (Universiti Teknologi MARA Cawangan Kelantan, 2020)
Islamic finance is making waves as a rapidly growingindustry within global finance. Experts are seeing numerous ingenious initiatives and activities to engage clear understanding of Islamic finance products.Nevertheless, the subject requires comprehensive and extensive reading to understand its applications in the real world. Hence, ‘Puzzling the Arrows’ is created to facilitate understanding and ease students’ learning of the subject. Using the puzzle-based learning, this product conceptualizesa new teaching and learning methodology focusing on the development of quick memorizing skills. The modus operandi of Islamic finance products, in terms of their structure, content and process, can be easily understood by learners through the use of Puzzling technique. More importantly, they will become more knowledgeable in understanding and mastering the products of Islamic finance. This innovation draws upon a diverse literature on Islamic finance knowledge and builds upon numerous issues raised by academics and practitioners in providing attractive platforms for mastering the Islamic finance knowledge